Three essays on the share structure reform in China - Zhu, Yanjian (2009)
In China, prior to April 29, 2005, about two thirds of all outstanding shares were mainly help by the government or government-linked agencies and cannot be traded in the open market. Only about one third of all outstanding shares, mainly held by individuals and some institutional investors, can be traded freely. The split structure casued many serious problems: e.g (1) deviation of price from fundamental values. The majority shareholders who made corporate policies and had the control of the company’s profits and assets were indifferent to the fluctuations on stock prices. Too many investors were chasing limited number of tradable shares. The stock market was more like a casino than in intermediary channel of capital; (2) weak corporate governance and minority shareholder protection. Over half of all outstanding shares are restricted from free trading. Takeovers in the open market seldom occur. Due to the certain historical reason, controlling shareholders have incentives to extract some wealth from listed companies at the expense of minority shareholders. Such incentives cannot be threatened by open-market takeovers. Minority tradable shareholders were weakly protected.